KETAHANAN 30 JENIS KAYU INDONESIA TERHADAP SERANGAN BUBUK KAYU KERING Heterbostrichus aequalias Waterh - Jasni (BRIN Publishing, 2015)
Thirty wood species originated from various regions in Indonesia were tested against powder-post beetle. Representative wood samples with the dimension of 7.5 cm x 5 cm x 2.5 cm were taken from each tree species and tested against powder post beetle (Heterbostrychus aequalias Waterh) for six weeks. Observation was carried out on the tested specimens, and the observed parameters comprised of the weight loss percentage and the survival rate of powder-post beetles. Besides, subjective observation was also performed on regard to the degree of the attack. The obtained data (i.e. wood-weight loss, beetles' survival rate, and degree of attack were further classified into five categories based on the resistance characteristics. Based on wood-weight loss revealed that as nine of the 30 wood species were regarded as class I (29.99%), three species as class II (9.97%), eight species as class III (26.67%), six species as class IV (19.99%), and four species as class V (13.33%). Pertaining to beetles survival rate, five species were categorized as class I (16.67%), three species as class II (9.99%), 12 species as class III (39.99%), eight species class IV (28.67%), and two species as class V (6.67%). Further, with regard to the degree of beetle attack, five species belong to the criteria of severely attacked (16.67%), whereas consecutively 16 species were classified as moderately attacked (53.33%) and nine species as slightly attacked (30%).